An analysis of the CSR portfolio of cruise shipping lines. (December 2022) - Geerts, Michaël; Dooms, Michaël
Abstract: This paper focuses on the Corporate Social Actions (CSAs) that five major cruise companies conduct in order to improve their Corporate Social Responsibility (CSR). Through a content analysis, we examine the most recent sustainability reports of the five largest cruise shipping companies, based on their market share. The analysis shows that CSAs in the domains of environment, ethics and social/philanthropy are dominant within the cruise industry. However, substantial differences are observed between the leading companies in the industry. At the level of both primary and secondary stakeholders, CSR is implemented at the peripheral level of the business. This observation points towards either a high and stringent level of existing regulation preventing further proactive behavior in the core business activities, or the potential high cost of developing core business-related CSAs, combined with long and uncertain payback times. The study leads to many suggestions for further research, as limitations arise from the lack of available data on the resources invested in CSAs, as well as in-depth information from the companies in terms of the reasons and motives to engage in specific CSR activities. Further research will also require the development of cruise industry-specific guidelines on CSR reporting, as the current reports differ widely in the amount of information provided as well as the generic standards used. Finally, as this research was conducted before the COVID19 pandemic, we believe the results may be significantly altered in the aftermath of the resulting crisis in the cruise industry.